Remarks on the Comprehensive Development Framework - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, remarked that the overwhelming pressure on the planet is a concern that affects all of us. The pressures on the environment, on health, on trade, on crime, on growth, on drugs, on immigration—all bring us close together in one planetary context. The Vietnamese economy is facing these issues as it tries to accommodate all these factors at the same time: the pressure of competition—competition for investment, the desire to relate the country to the international trading system, and the desire to create an environment which is hospitable to domestic and foreign investors and which spreads the wealth throughout in an equitable way. Through the Comprehensive Development Framework, the country should lead its citizens, civil society, the private sector, and the international institutions to set up not a series of projects but programs. These programs will identify the issues to be addressed over the next 10 years or 15 years. There needs to be some comprehensive form of review of process, and review of plans so that one can have an integrated approach, an approach that can be leveraged, that is participatory and that engages each sector of society.